Changes in the Species and Functional Composition of Activated Sludge Communities Revealed Mechanisms of Partial Nitrification Established by Ultrasonication - Xue, Yu; Zheng, Min; Wu, Shuang; Liu, Yanchen; Huang, Xia (Frontiers in Microbiology, 2022)
To achieve energy-efficient shortcut nitrogen removal of wastewater in the future, selective elimination of nitrite-oxidizing bacteria (NOB) while enriching ammonia-oxidizing microorganisms is a crucial step. However, the underlying mechanisms of partial nitrification are still not well understood, especially the newly discovered ultrasound-based partial nitrification. To elucidate this issue, in this study two bioreactors were set up, with one established partial nitrification by ultrasonication while the other didn't. During the operation of both reactors, the taxonomic and functional composition of the microbial community were investigated through metagenomics analysis. The result showed that during ultrasonic partial nitrification, ammonia-oxidizing archaea (AOA), Nitrososphaerales, was enriched more than ammonia-oxidizing bacteria (AOB), Nitrosomonas. The enrichment of microorganisms in the community increased the abundance of genes involved in microbial energy generation from lipid and carbohydrates. On the other hand, the abundance of NOB, Nitrospira and Nitrolancea, and Comammox Nitrospira decreased. Selective inhibition of NOB was highly correlated with genes involved in signal transduction enzymes, such as encoding histidine kinase and serine/threonine kinase. These findings provided deep insight into partial nitrification and contributed to the development of shortcut nitrification in wastewater treatment plants.